Implementasi Metode Penemuan Terbimbing untuk Meningkatkan Hasil Belajar Siswa pada Penarikan Kesimpulan Logika Matematika - Nurcholis, Nurcholis (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
This research aim to obtain a description of the implementation of guided discovery method in improving student learning outcomes in mathematical logic inference matter. The research design refers to the design of the research consisted of planning, action, observation, and reflection. Based on the results of research, performed the steps in learning with guided discovery method is to formulate the problem, analyze the data, develop conjectures, and make conclusions.